Spatial planning with obstacles. 40 years of spatial planning in crisis regions and developing countries. - (:unkn) unknown (Selbstverl., 2009)
After several decades of dedication and commitment to the School of Spatial Planning (TU Dortmund University), Prof. Dr. rer. nat. Volker Kreibich and Prof. Dr. rer. pol. Günter Kroës retired officially in 2006. Despite this, both of them are still very active being involved in many research projects and academic activities contributing to discussions with their experience and knowledge. The 40th anniversary of the School of Spatial Planning and the 25th anniversary of the international SPRING Master Programme in 2009 seem to be a good occasion to reflect upon their work. The publication on hand highly appreciates the pre- and post-retirement activities of the two professors by bringing together a collection of articles contributed by some of their colleagues, companions and alumni. Although the fields of interest of Prof. Kreibich and Prof. Kroës were manifold the overall frame of the publication can be summarised as Spatial Planning with Obstacles - 40 Years of Spatial Planning in Crisis Regions and Developing Countries .
Spatial planning with obstacles. 40 years of spatial planning in crisis regions and developing countries.
Keywords: Raumplanung; Raumentwicklung; Stadtentwicklungsplanung; Entwicklungsland; Siedlungsstruktur; Planungstheorie; Planungsmodell; Planungsprozess; Fallstudie; Konflikt; Krieg; Krise